Sensacional telegrama del Sr. Tous Soto - Tous Soto, José (My University, 1924)
Recorte de periódico sobre el Manifiesto de 1924
Keywords: Tous Soto, José, 1874-1933; Barceló, Antonio R., 1868-1938; Partido Republicano (Puerto Rico)